Light intensity drives regeneration in fragmented mushroom coral Lithophyllon repanda anthocaulus and anthocyathus more than the spectra - WIDIASTUTI WIDIASTUTI; NADIRA PUTRI DIWANTI; AGNESYA AGNESYA; NIKEN MAYUNI PUTRI; KADEK MIKO PURNAMA AGUSTINI; ACHMAD RAMADHAN; RIAN PRASETIA (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Widiastuti, Diwanti NP, Agnesya, Putri NM, Agustini KMP, Ramadhan A, Prasetia R. 2025. Light intensity drives regeneration in fragmented mushroom coral Lithophyllon repanda anthocaulus and anthocyathus more than the spectra. Biodiversitas 26: 5258-5266. Aquaculture offers a sustainable approach to meeting the high demand in the international ornamental aquarium trade for coral species within the family Fungiidae. Fragmentation, which is the most predominant form of asexual reproduction in the family Fungiidae, helps corals to survive anthropogenic and natural threats. This study aimed to investigate the regeneration phase and time of the artificially fragmented anthocaulus (an attached stalk-like structure) and anthocyathus (a mushroom-like structure) in the mushroom coral Lithophyllon repanda under different light spectra (blue and white lights) and intensities. The anthocaulus was horizontally fragmented from its anthocyathus, which was grown under different light spectra and at various intensities (n = 9 per treatment) for 166 days in controlled aquaria. The regenerations were observed and photographed under a stereomicroscope every 2 days. The results demonstrated that, despite differences in light properties, similar regeneration phases were observed in both fragmented anthocaulus and anthocyathus. Moreover, there was no significant difference in the regeneration time to develop primary polyps on the fragmented anthocaulus and recovered anthocyathus under different light spectra; however, they significantly regenerated and recovered faster at intensities of 130-54 µmol m-2 s-1 for less than 30 days. It implies the vital role of light intensities on the production of new polyps and regeneration of fungiid corals ex situ.